MUŠKI RUKOMET NA TERITORII NEKADAŠNJE JUGOSLAVIJE - USPJEHI IN TRANSFERI IGRAČA - Marta Bon; Bojan Leskošek; Mojca Doupona Topič (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
The following research analyses success of men's handball and transfers of handball players in the teritory of former Yugoslavia. The sample of measured subjects included 1266 players who moved from a club in one country to another club in a different country within Europe between 1996 and 2006. Data used were obtained from the EHF (European Handball Federation). In general we can say that Yugoslavia had one of the best national team in the world (regarding results on the Olympic Games). In the time of SFRY Croatian men handball team won the most club titles. Also after the year 1991, Croatian national men handball team has been the most successful. 27% of all transfers are made by Croatian handball players. Frequence of transfers was very hihg in the theritory of former Yugoslavia. In avarage, 126 players moved from club to club every year. The avarage ages of first transfer of the handball players were 24,6 years. In the analysed period male handball players were transferred more times (70,6%) than female players. We found several reasons for high number of transfers but the most important reasons are the quality level of handball national team and the success of Yugoslav clubs.